DISTRIBUTION OF HEAT WASTE IN TIDE ON THE PLTU AREA (THERMAL POWER STATION) SIRIH BAY, PADANG PROVINCE WEST SUMATERA - Al Hamda, Teguh Cakra; Mubarak, Mubarak; Galib, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT The level of electricity usage needs continues to increase each year in line with increased economic growth. One of the technologies used in producing electricity is the PLTU (Thermal Power Station) where PLTU Teluk Sirih is the first PLTU in West Sumatra that has been operating since 2013 and has a capacity of 2x112 MW. The existence of a power plant in the waters of Sirih Bay is thought to affect the characteristics of these waters. This is because besides producing electricity, it also produces hot water waste from the process of absorbing hot steam that enters the coastal waters through the outlet channel. The purpose of this study was to determine the distribution process of hot water waste from PLTU Teluk Sirih at high tide and ebb with field data and hydrodynamic modeling of waters, as well as sea surface temperature observation data at 16 sampling points. Verification of field data and hydrodynamic models has a Root Mean Square Error (RMSE) value of 5.74% (e = 0.015). The pattern of ocean circulation in the waters of the Sirih Bay Coast is mainly controlled by the tidal force, where the flow pattern at the time of the tides goes northeast with some moving towards the southwest. Observations show the temperature of the waste of hot water in the outlets until the sea in front of them is recorded between 32 °c to 35 °c. Horizontally, the delusional zone of the waste heat reaches a radius of 500 m from the mouth of the outlet where the waste heat occurs more broadly during low tide conditions. Keywords : PLTU Teluk Sirih, Heat Waste, Hydrodynamic Model